Antioxidant activity, fatty acid profile and tocopherols of Tamarindus indica L. seeds - Moreno Luzia, Debora Maria [UNESP]; Jorge, Neuza [UNESP] (Soc Brasileira Ciência Tecnologia Alimentos, 2011)
This study aimed to characterize Tamarindus indica L. seeds regarding its composition and to evaluate its antioxidant potential, fatty acid profile and content of tocopherols. In order to obtain the extract, the dried and crushed seeds were extracted with ethanol for 30 minutes in a 1:3 seeds: ethanol ratio under continuous stirring at room temperature. After that, the mixtures were filtered and subjected to roto-evaporation at 40 degrees C in order to determine, through direct weighing, the dry matter yields of the extracts. According to the results, Tamarindus indica L. seeds showed high content of total carbohydrates (71.91%) and offered relevant content and antioxidant activity of phenolic compounds. Tamarindus indica L. seeds oil presents high oxidative stability (15.83 hours) and significant total tocopherol content (57.77 mg.kg(-1)), besides presenting a higher percentage of unsaturated fatty acids - the main component being linolenic (59.61%), which is considered an essential fatty acid.
Atividade antioxidante, perfil de ácidos graxos e tocoferóis de sementes de Tamarindus indica L.
Keywords: Tamarindus indica L.; oils; Gas chromatography